Synthesis of peptides and pyrazines from beta-aminoalcohols via extrusion of H2 catalyzed by ruthenium pincer complexes. ligand controlled selectivity - Gnanaprakasam, Boopathy; Balaraman, Ekambaram; Ben-David, Yehoshoa; Milstein, David (Angewandte Chemie, 2011)
Bitte wählen: Die Wahl des Katalysators, eines Ru-Pinzettenkomplexes, bestimmt, ob Peptide oder Pyrazine aus β-Aminoalkoholen entstehen: Der PNN-Komplex 1 führt, je nach Substituent R (siehe Schema), zu linearem Polyalanin oder zu cyclischen Dipeptiden, der PNP-Komplex 2 katalysiert die Bildung von Pyrazinen. Die Reaktionen finden in homogener Lösung unter neutralen Bedingungen statt.

Synthesis of polyamides from diols and diamines with liberation of H2 - Gnanaprakasam, Boopathy; Balaraman, Ekambaram; Gunanathan, Chidambaram; Milstein, David (Journal of Polymer Science Part A: Polymer Chemistry, 2012)
The amidation reaction based on catalytic coupling of alcohols with amines previously reported by us, using the pincer complexes 1 and 2 as catalysts, was applied to the generation of polyamides from nonactivated diols and diamines. A range of polymers was prepared, with Mn up to 26.9 kDa. Unlike the traditional syntheses of polyamides based on carboxylic acid derivatives, which require the use of toxic reagents and generate stoichiometric amounts of waste, this process generates only molecular hydrogen as byproduct. Both aromatic and aliphatic diols and diamines were used. Gel permeation chromatography measurements of the dimethylformamide-soluble polymers and thermal studies of the polyamides were performed. Matrix assisted laser desorption/ionization time-of-flight (MALDI-TOF) spectra are also reported. Thermogravimetric analyses studies indicate that the aromatic polyamides (with the exception of the pyridine-based polyamide) are more thermally stable than the aliphatic ones. This general, environmentally benign method for the synthesis of polyamides is homogeneously catalyzed under neutral conditions by dearomatized ruthenium-pincer complexes 1 and 2 and proceeds in 1,4-dioxane under an inert atmosphere. Conditions for polyamidation in the absence of solvent are also reported, using the pincer complex 2 as catalyst. © 2012 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem, 2012